Livelihood security of small and marginal farmers through Ocimum cultivation - Suryavanshi, Priyanka; Kumar, Dipender (Indian Horticulture, 2021)
In view of achieving the target of doubling farmers income by March 2022, there is a need to identify crops and varieties that may suit resource poor farmers. Introduction, adaption and acceptance of new crops, varieties and latest technical knowhow for crop production can potentially strengthen farmers’ cropping systems by increasing yields, improving drought resilience and also by capturing new market opportunities. In this context, ocimum cultivation may be adopted by small and marginal farmers of India. It is a miracle plant which is valued for its medicinal properties. It has been harvested for use in Ayurveda treatments for 5,000 years and is known as the ‘Queen of Herbs’. Essential oil of ocimum is widely used in perfumery, cosmetics, pharmaceuticals and confectionary industries. Farmers may adopt ocimum cultivativation in rainfed areas in Kharif season as it requires lower input and gives better returns, thus it has the potential of enhancing farmers income.